Geoecologia das paisagens aplicada ao turismo comunitário na terra indígena Lagoa Encantada do povo Jenipapo-Kanindé – Aquiraz/CE - Oliveira, Vitória Valentim de (2023)
The way mass tourism is developed in the globalized world leads to the trend of private appropriation of public spaces, making them increasingly segregated. The notion of modernity that makes up the activity ends up mischaracterizing places, cultures and identities when directed by segregating market-based visions. The populations of the coastal regions of Ceará have suffered the implications arising from this activity with greater effect, for example, there are traditional communities, which are having to adapt to this form of economy so as not to be pushed to the margins of the new processes functioning of the coast through tourism. The Jenipapo-Kanindé indigenous people are located in the Lagoa Encantada Indigenous Land, in the district of Jacaúna, Aquiraz/Ceará/Brazil. The ethnic group has carried out community tourism activities on their lands with the aim of diversifying the community's economy and protecting it’s natural resources. Based on this, this study aims to carry out a geoecological analysis of the landscapes of the Lagoa Encantada Indigenous Land, highlighting the environmental systems and cultural conditions with their potential, problems and limitations, as a way of subsidizing the development of community tourism for the community. The theoretical-methodological precepts of Landscape Geoecology are taken as the basis for the development of this work, which is divided into four stages: organization and inventory, analysis, diagnosis and propositions. It was possible to detail the geoenvironmental characteristics: geology, geomorphology, soil, climate, hydrology and vegetation; in addition to compartmentalizing the area into landscape units and subunits, namely: coastal plain (beach and post-beach; dune field; fluvio-marine plain and fluvio-lacustrine plain) and pre-coastal plateau. The socio-environmental diagnosis of I.L with its problems, limitations and potential made it possible to organize proposals for management strategies and development of community tourism in the area through environmental zoning, which was divided into five zones: Landscape Preservation Zone; Environmental Recovery Zone; Agroproductive Conservation Zone; Residential Expansion Zone; Specific Use Zone for Community Tourism. The study seeks to effectively contribute to improving the management and conservation of the natural and cultural landscapes of I.L Lagoa Encantada and strengthening community tourism activities.